Alpha-factor structural gene mutations in Saccharomyces cerevisiae: effects on alpha-factor production and mating. - Kurjan, J (1985)
The role of alpha-factor structural genes MF alpha 1 and MF alpha 2 in alpha-factor production and mating has been investigated by the construction of mf alpha 1 and mf alpha 2 mutations that totally eliminate gene function. An mf alpha 1 mutant in which the entire coding region is deleted shows a considerable decrease in alpha-factor production and a 75% decrease in mating. Mutations in mf alpha 2 have little or no effect on alpha-factor production or mating. The mf alpha 1 mf alpha 2 double mutants are completely defective in mating and alpha-factor production. These results indicate that at least one alpha-factor structural gene product is required for mating in MAT alpha cells, that MF alpha 1 is responsible for the majority of alpha-factor production, and that MF alpha 1 and MF alpha 2 are the only active alpha-factor genes.